2011
DOI: 10.1016/s1474-4422(11)70072-2
|View full text |Cite
|
Sign up to set email alerts
|

The projected effect of risk factor reduction on Alzheimer's disease prevalence

Abstract: There are currently approximately 33.9 million individuals with Alzheimer's disease (AD) worldwide, and prevalence is expected to triple over the next 40 years. The goal of this review was to summarize the evidence regarding seven potentially modifiable AD risk factors: diabetes, mid-life hypertension, mid-life obesity, smoking, depression, low educational attainment and physical inactivity. In addition, we projected the impact of risk factor reduction on AD prevalence by calculating population attributable ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

48
1,819
9
64

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 2,283 publications
(1,990 citation statements)
references
References 92 publications
48
1,819
9
64
Order By: Relevance
“…1,13,14 There is increasing evidence to support an association between Alzheimer's disease and cardiovascular risk factors such as hypertension and hypercholesterolaemia. [15][16][17] It has been argued that in older age groups Alzheimer's disease should be considered as a diffuse clinical syndrome representing the gradual accumulation of multiple pathologies rather than as a discrete neuropathological entity. 15 Health-care delivery for people with dementia and comorbidity Comorbidity among people with dementia presents particular challenges for primary and secondary care.…”
Section: Dementia and Comorbiditymentioning
confidence: 99%
“…1,13,14 There is increasing evidence to support an association between Alzheimer's disease and cardiovascular risk factors such as hypertension and hypercholesterolaemia. [15][16][17] It has been argued that in older age groups Alzheimer's disease should be considered as a diffuse clinical syndrome representing the gradual accumulation of multiple pathologies rather than as a discrete neuropathological entity. 15 Health-care delivery for people with dementia and comorbidity Comorbidity among people with dementia presents particular challenges for primary and secondary care.…”
Section: Dementia and Comorbiditymentioning
confidence: 99%
“…However, more recent and complete demographic studies have shown that smoking represents one of the largest risk factors for AD 3,[19][20][21][22] . To study the effect of cigarette smoking on the onset of brain alterations typical of AD, we exposed mice, genetically engineered to develop some of the neuropathological features of AD, to complete tobacco smoke, under similar conditions in which smokers are exposed to this material.…”
Section: Nature Communications | Doi: 101038/ncomms2494mentioning
confidence: 99%
“…Other AD lesions include a massive inflammatory response, characterized by activated microglia and reactive astrocytes, synaptic impairment and neuronal loss in selective areas of the brain 1,2 . The aetiology of sporadic AD is not well known, but several risk factors have been shown to increase the probability of developing the disease 3 . Although the main risk factor for AD is aging, various others factors have also been proposed, including gender, ApoE polymorphism, the coexistence of other disorders (such as cardiovascular diseases, brain injury, diabetes and Down syndrome) and several lifestyle conditions, including physical activity, education, diet or smoking 4,5 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of curative therapy, current research is interested in prevention by identifying subtle signs of early-stage neurodegeneration. Crucially, early diagnosis would provide a critical opportunity for disease-modulating interventions targeting modifiable risk factors for AD or PD (Barnes and Yaffe 2011), or even neuroprotective therapies, which both would help delay, slow, or even prevent disease progression (i.e., more cases would remain in the mild stage rather than degrade to moderate or severe stages; Petersen 2009). …”
Section: Introductionmentioning
confidence: 99%